2017
DOI: 10.3390/ani7030016
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Cows Produce Less Milk and Modify Their Behaviour during the Transition between Tie-Stall to Free-Stall

Abstract: Simple SummaryThe purpose of this study was to evaluate the influence of moving cows from the barn with stanchion-stall housing to free-stall housing on their behaviour and production. Cows lay down up to ten hours after removing. The cows in their second lactation and open cows tended to lie sooner after removing than cows in their first lactation and pregnant cows. The times of total lying and rumination were increasing from the first day to the tenth day after removing. Cows produced 23.3% less milk at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 52 publications
1
18
0
1
Order By: Relevance
“…For this study, animals were confined in a pen and selected from different productive herds. Broucek et al, [23] reported that transferring lactating dairy cows to unknown pens with unknown animals might result in signs of stress that include a long-term suppression of milk efficiency and overall production performance.…”
Section: Resultsmentioning
confidence: 99%
“…For this study, animals were confined in a pen and selected from different productive herds. Broucek et al, [23] reported that transferring lactating dairy cows to unknown pens with unknown animals might result in signs of stress that include a long-term suppression of milk efficiency and overall production performance.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of maturation on laterality in ungulate livestock therefore seems to be more complex and requires further study. Some studies in adult cattle have reported increased right laterality during lying in older cattle [132,147] and an increased preference for using the right eye in fights [144]. These findings are in contrast to findings in primates, where laterality was found to decrease in older age [194] and thereby provide interesting new insights into how laterality changes throughout the lifespan.…”
Section: Development Of Laterality and Sex Differencesmentioning
confidence: 88%
“…These results suggest that chronic presentation of an emotionally relevant stimulus may influence somatic functions and consequently improve both productive and reproductive performance. Other studies also suggest that a left bias during lying may be associated with pregnancy in cows [75,77,79,132,147], which is most likely due to the position of the fetus [78]. In horses, performance in different types of tasks such as dressage and racing was found to be associated with laterality.…”
Section: Production and Performancementioning
confidence: 94%
“…Behavioral changes do not always occur in an adaptive and beneficial way (2). In some cases, they may indicate health problems, emotional disturbance, and stress (4) and may influence animal productivity (5).…”
Section: Introductionmentioning
confidence: 99%